Studi Kualitatif tentang Peran Madrasah Tsanawiyah Pesantren Ilmu Quran dalam Meningkatkan Mobilitas Sosial Siswa - Stevany Nurvita, Amanda; Yasin, Muhammad (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2025)
Madrasah Tsanawiyah Islamic Boarding School for Quran Sciences is one of the educational institutions that contributes to efforts to increase social mobility. This research aims to understand the role of the Madrasah Tsanawiyah Islamic Boarding School for Quran Sciences in increasing the social mobility of its students. Social mobility, which refers to the movement of individuals or groups between social dimensions, has become important in the modern educational context. The research uses descriptive qualitative methods, with data collection through observation, interviews and documentation. The research results show that madrasas function as a bridge that connects religious values ​​with general knowledge, as well as providing support through quality teaching staff, adequate facilities, and parental involvement. Factors such as close supervision and extracurricular activities also contribute to increasing students' social mobility. The main way that the Madrasah Tsanawiyah Islamic Boarding School for Quran Sciences has to increase the social mobility of its students is through maximizing efforts to fulfill existing supporting factors. Thus, Madrasah Tsanawiyah Islamic Boarding School for Quran Sciences has a significant role in facilitating changes in the social and economic status of students, preparing them to contribute positively to society.